PERANCANGAN PROTOTIPE UI/UX LAYANAN PEMESANAN BERBASIS MOBILE WEBSITE PADA UMKM LETRA STUDIO MENGGUNAKAN METODE DESIGN THINKING - Brilioneristen; Mia Juliana; Made Nindya Kirana (Jurnal Riset Multidisiplin Edukasi, 2025)
Letra Studio, an MSME photography studio in Jimbaran, faces challenges with its manual reservation system via social media: slow responses, risk of double booking, data management difficulties, and lack of transparency regarding prices and schedules. This process takes over an hour, far exceeding customer expectations of under ten minutes, and results in a System Usability Scale (SUS) score of 45.4 ("Poor"). This study designs a UI/UX prototype for a mobile website-based ordering service at Letra Studio using the Design Thinking method (Empathize, Define, Ideate, Prototype). This high-fidelity prototype integrates real-time schedule display, structured package information, and an automated payment flow. Usability testing with 12 participants showed positive results: a 100% Completion Rate, an average booking time of 127.5 seconds (significantly more efficient than the >1 hour manual process), and a SUS score of 92 ('A' / 'Excellent'). In conclusion, the UI/UX prototype design successfully created an effective, comfortable, and efficient customer experience, significantly reducing booking time, addressing pain points, and enhancing Letra Studio's professionalism and operational efficiency.